Adsorption Study of Heavy Metals Cu and Cd by Ciapus Zeolite Activated Physically and Chemically with Acid - Nurdiani M.Si.; Ulaa Safani (Politeknik AKA Bogor, 2026)
Natural zeolite has been widely explored as an adsorbent to reduce heavy metal contamination, particularly copper (Co) and cadmium (Cd), in the environment. This study aimed to evaluate the characteristics, adsorption capacity, and adsorption kinetics of natural zeolite toward Cu and Cd ions. The zeolite was activated physically at 400°C for 3 hours and chemically using 0.5 M HCl for 30 minutes to enhance its adsorption performance. Characterization was conducted using FTIR, BET, and SEM analyses. FTIR results confirmed the presence of Si–O–Si and Si–O–Al functional groups at 1007.49 cm⁻¹, indicating the typical aluminosilicate structure of zeolite. BET analysis showed that zeolite has a larger surface area compared to eggshell, while SEM images revealed the presence of porous structures after activation. Adsorption experiments indicated that the maximum adsorption capacities were 0.139 mg/g for Cu and 0.169 mg/g for Cd. The optimum contact time for both metals was 30 minutes at concentrations of 10 mg/L for Cu and 15 mg/L for Cd. Kinetic studies demonstrated that the adsorption process followed a pseudo-second-order model, with rate constants of 0.0001 min⁻¹ for Cu and 0.0002 min⁻¹ for Cd, suggesting chemisorption as the dominant mechanism